Past, Present, and Future Strategies for Enhanced Assessment of Embryo's Genome and Reproductive Competence in Women of Advanced Reproductive Age - Poli, Maurizio; Girardi, Laura; Fabiani, Marco; Moretto, Martina; Romanelli, Valeria; Patassini, Cristina; Zuccarello, Daniela; Capalbo, Antonio (Frontiers in Endocrinology, 2019)
Recent advancements in genomic analysis allow testing of an increasing number of genetic features in human preimplantation embryos. Typical single gene mutation and whole chromosomes testing can now be integrated with assessment of mitochondrial DNA and polygenic conditions. Diagnostic expansion into epigenetic and transcriptomic assessment in the near future are potential technological targets which may improve the prognostic outlook of patients of advanced reproductive age and overall in vitro fertilization (IVF) treatment outcomes. In this review, we discuss the technological progress of recent years and their future applications in preimplantation genetic testing in IVF.